A Novel Antifungal Actinomycete Streptomyces sp. Strain H3-2 Effectively Controls Banana Fusarium Wilt - Zou, Niexia; Zhou, Dengbo; Chen, Yinglong; Lin, Ping; Chen, Yufeng; Wang, Wei; Xie, Jianghui; Wang, Mingyuan (Frontiers in Microbiology, 2021)
Banana Fusarium wilt disease caused by Fusarium oxyspoum f. sp. cubense (Foc) seriously threatens banana industry. Foc tropical race 4 (Foc TR4) can infect almost all banana cultivars. Compared with traditional physical and chemical strategies, biocontrol using benefit microbes is considered as an environmentally sound option to manage fungal disease. In this study, a strain H3-2 was isolated from a banana orchard without disease symptoms of Fusarium wilt for more than ten years and exhibited a high antifungal activity against Foc TR4. According to its morphological, physiological, and biochemical characteristics, strain H3-2 was identified as Streptomyces sp. The result was supported the polymorphic tree constructed using the 16S rRNA sequence. Strain H3-2 extracts could destroy the membrane integrity and the mycelial ultrastructure of Foc TR4 cells. In addition, the mycelial growth and the spore germination were also inhibited. Notably, the strain and its extracts showed a broad-spectrum antifungal activity against seven selected fungal phytopathogens. Fourteen chemical compounds in strain H3-2 extracts were identified by gas chromatography-mass spectrometer (GC-MS). Phenolic compounds were the primary components. A pot experiment demonstrated that the fermentation broth of strain H3-2 inhibited efficiently the spread of banana Fusarium wilt disease and promoted the growth of banana seedlings. Hence, Streptomyces sp. H3-2 has a potential function microbe for the management of banana Fusarium wilt.